The Ruling on Seeking knowledge Electronically in Islamic Law (A Comparative Jurisprudential Study) (Islamic Sciences Journal, 2025)
Seeking knowledge is one of the most important topics that preoccupies Muslims of all levels of knowledge. Sharia knowledge is what connects a Muslim to his Lord. Just as Islamic law is the law that is valid for all times and places, it must keep pace with the modern era. Therefore, I have explained the Sharia ruling on seeking knowledge electronically. I do not see any objection to that if it is done according to controls and conditions. Seeking knowledge through traditional methods is no different from seeking it electronically in terms of legitimacy. However, I believe that seeking knowledge electronically facilitates many matters that are among the difficulties facing the seeker of knowledge through traditional methods. In the modern era, it is difficult for a seeker of knowledge to devote himself completely to seeking knowledge through traditional methods. A person cannot leave work and earning a living to devote himself to seeking knowledge. Also, seeking knowledge through traditional methods requires traveling and devoting time, which makes it difficult for the seeker of knowledge. Also, some people with special needs find it difficult to seek knowledge due to the difficulty of travel and movement. Also, women may find it difficult to leave their homes to seek knowledge due to the domestic responsibilities that fall on their shoulders. Seeking knowledge electronically overcomes all these difficulties for them, and its merit is conditional upon the availability of the conditions of validity. The application and its etiquette, taking into account the shortcomings and working to avoid them
Keywords: Ruling, seeking knowledge, electronically, Islam, Sharia